Exploring the Relationship between Accreditation and Patient Satisfaction - The Case of Selected Lebanese Hospitals - Wissam Haj-Ali; Lama Bou Karroum; Nabil Natafgi; Kassem Kassak (Kerman University of Medical Sciences, 2014)
Background Patient satisfaction is one of the vital attributes to consider when evaluating the impact of accreditation systems. This study aimed to explore the impact of the national accreditation system in Lebanon on patient satisfaction. Methods An explanatory cross-sectional study of six hospitals in Lebanon. Patient satisfaction was measured using the SERVQUAL tool assessing five dimensions of quality (reliability, assurance, tangibility, empathy, and responsiveness). Independent variables included hospital accreditation scores, size, location (rural/urban), and patient demographics. Results The majority of patients (76.34%) were unsatisfied with the quality of services. There was no statistically significant association between accreditation classification and patient satisfaction. However, the tangibility dimension - reflecting hospital structural aspects such as physical facility and equipment was found to be associated with patient satisfaction. Conclusion This study brings to light the importance of embracing more adequate patient satisfaction measures in the Lebanese hospital accreditation standards. Furthermore, the findings reinforce the importance of weighing the patient perspective in the development and implementation of accreditation systems. As accreditation is not the only driver of patient satisfaction, hospitals are encouraged to adopt complementary means of promoting patient satisfaction.